Obliterative cholangiopathy in acquired cystic biliary atresia type III after cyst perforation: a case report - Tsugumichi Koshinaga; Kensuke Ohashi; Kakou Ono; Hide Kaneda; Takeshi Furuya (BMC, 2018)
Abstract Background In biliary atresia, the disease process of obliterative cholangiopathy may begin in the perinatal period; however, no chronological evidence exists on how the cholangiopathy progresses to biliary obliteration. This is the first acquired case with the final diagnosis of type III cystic biliary atresia with an extrahepatic biliary cyst which showed the progression of obliterative cholangiopathy in chronological order after birth. Case presentation An 81-day-old girl presented with acute abdominal distress due to bilious peritonitis caused by biliary cyst perforation, for which she underwent emergency biliary drainage. Postoperative images showed a dilated common bile duct and hepatic ducts bilaterally, with flow of the contrast medium to the duodenum through the dilated common bile duct. Biochemistry of the bile collected during and after the operation revealed elevated levels of pancreatic enzymes in the bile from the gallbladder. The patient was diagnosed as having a congenital choledochal cyst and underwent laparotomy at 120 days of age which revealed that she had pancreaticobiliary maljunction. The biliary cyst was resected at the narrow portion just above the junction with the main pancreatic duct. During dissection up to the hepatic hilum, we found that the hilar hepatic ducts were bilaterally replaced by fibrous tissue and were obstructed, leading to a diagnosis of type III a1, μ biliary atresia. The fibrous tissue was excised, and hepatic portoenterostomy was performed according to the Kasai procedure. The patient's postoperative course was uneventful and the jaundice resolved within 1 month. She has had normal liver function tests with no episode of cholangitis for 3 years after discharge. Conclusions We demonstrated the process of acquired type III biliary atresia in a patient with cystic biliary atresia and biliary cyst perforation. To the best of our knowledge, this is the first case of acquired cystic biliary atresia showing chronological progression of the course of obliterative cholangiopathy, providing a better understanding of the development of type III biliary atresia as an acquired disease.